Efecto de la aplicación de cuatro abonos orgánicos en el desarrollo del cafeto en la Estación Experimental la Argelia - Cordero Escobar, Jonathan Andrés (2024)
Coffee is recognized worldwide as a crop of economic importance, especially for farmers. Locally, the province of Loja has obtained national and international recognition for producing high quality coffee; therefore, it is essential to implement technologi es that increase productivity and at the same time preserve the environment. Therefore, the objective of the current research was to evaluate the development of the coffee crop established without shade with an age of four years after the application of or ganic fertilizers in the Quinta Experimental Docente La Argelia of the National University of Loja . The experimental design was completely randomized blocks in which four treatments were established: Azolla bocashi (T1), pollinaza bocashi (T2), Nutrisano (T3), Eco abonaza (T4) and control (T5), with three replicates, obtaining a total of 15 experimental units. The variables evaluated were plant height, stem diameter, leaf area, chlorophyll content (SPAD), stomatal conductance, density and stomatal index. Th e best results were obtained at 150 DDA with the treatment of pollina za bocashi and Azolla bocashi, which presented the highest averages in comparison with the commercial brand fertilizers and the control. In conclusion, the use of organic fertilizers contributes to the development of the Sarchimor coffee crop.